Highly dispersible graphene oxide reinforced polypyrrole/polyvinyl alcohol blend nanocomposites with high dielectric constant and low dielectric loss. Issue 76 (19th August 2015) - Deshmukh, Kalim; Ahamed, M. Basheer; Pasha, S. K. Khadheer; Deshmukh, Rajendra R.; Bhagat, Pundlik R.
<x xml:space="preserve">Abstract</x> In the present study, we report the fabrication and characterizations of flexible dielectric nanocomposites consisting of water soluble polypyrrole (WPPy)/polyvinyl alcohol (PVA)/graphene oxide (GO) at different GO loadings (0.5–3 wt%).